Strategi Manajemen Konflik Komunikasi Organisasi Pencak Silat: Studi Kasus pada Organisasi Persaudaraan Setia Hati Terate (PSHT) Rayon Semolowaru Elok dalam Meminimalisir Konflik di Surabaya - Syaikhul Ulum; Yudiana Indriastuti (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Conflict is always present in every relationship between individuals and groups in various conditions and events. Communication in an organization is really needed to improve the organization, besides that, communication is also very important for the progress of the organization. An organization can be said to be successful if the communication relationship between internal parties and external parties is harmonious. The Terate Faithful Brotherhood Organization (PSHT) as a research object is based on the researcher's observations that this organization is also often involved in conflict or friction with other organizations in the city of Surabaya. The aim of this research is to find out more about the communication conflict management strategy of the Semolowaru Elok Rayon Faithful Brotherhood (PSHT) organization in minimizing the occurrence of conflict between pencak silat organizations in Surabaya. This research uses descriptive qualitative research using the conflict management strategy of Dean G. Pruitt & Jeffrey Z. Rubin. The research results show that internal conflicts and external conflicts that occur are the actions of individuals. The individuals in this case are individuals who are members of a martial arts school but abuse the teachings of a pencak silat organization to carry out actions that cause conflict. Handling measures for individual members in minimizing the occurrence of conflict, the pencak silat organization must educate from students to members through character, instilling values, norms, laws as well as involving the positive activities of the pencak silat organization and abandoning the negative activities of other members.